Southwest Research-Extension Center Field Day 2019 - R. Gillen (Kansas Agricultural Experiment Station Research Reports, 2019)
Agricultural research was conducted at the Southwest Research-Extension Center in Kansas. Topics include cropping, tillage, soil fertility, and weed science.
Keywords: cropping; tillage; soil fertility; weed science